Breaking the Silence: Understanding the Struggles of Students in Academic Speaking Courses - Fajarina, Maskhurin; Sumanto, Ossa Bodhi Tala (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
Academic speaking is one of the most challenging skills for university students in English as a Foreign Language (EFL) contexts. Despite years of English learning, many students remain silent, anxious, and hesitant to participate in academic discussions. This qualitative study investigates the underlying struggles faced by EFL students at Universitas Hasyim Asy’ari (UNHASY) in Academic Speaking courses. Using classroom observations and semi-structured interviews with fifteen English Education Department students, the study explores the psychological, linguistic, and pedagogical factors that contribute to classroom silence and speaking anxiety. Thematic analysis revealed three dominant struggles: (1) affective barriers such as fear of negative evaluation, perfectionism, and low self-efficacy; (2) linguistic challenges including limited vocabulary, pronunciation difficulties, and lack of academic discourse knowledge; and (3) environmental constraints such as teacher-centered instruction, insufficient scaffolding, and peer judgment. The findings highlight that silence in academic speaking classes is not mere passivity but a reflection of deeper cognitive and emotional conflicts. The study suggests that integrating reflective and deep-learning pedagogies, fostering supportive classroom communities, and promoting self-efficacy can significantly improve students’ confidence and engagement in academic speaking. The results contribute to the growing body of literature on affective factors in language learning and provide pedagogical implications for improving EFL speaking instruction in higher education contexts.